The Communication Patterns between Online Transportation Applicators and Driver Partners in Bandung - Hidayat, Dasrun; Aliya Azrifatin, Anis; Gusdianto, Adi (UPT Publikasi Ilmiah UNISBA, 2023)
The online transportation industry is growing rapidly in the city of Bandung. Therefore, understanding the public relations communication patterns applied by online transportation applicators is very important. Effective communication patterns can strengthen relationships, increase trust levels, and increase partner loyalty to the company. However, if the communication pattern is not appropriate, it can cause obstacles, conflicts, and partner dissatisfaction. This study aims to analyze the communication patterns of public relations in online transportation applications with driver partners in the city of Bandung. The research method is descriptive-qualitative, with data collection techniques through interviews with eight driver partners of online transportation applications. The scientific findings show that communication barriers between applicators and driver-partners are related to differences in language, culture, communication understanding, and limited communication channels. However, applicators have implemented persuasive communication approach strategies by providing communication channels such as online forums and offline meetings to facilitate communication with partners. In conclusion, the importance of understanding and handling communication barriers in the public relations relationship between online transportation applicators and driver-partners Effective communication and the use of appropriate communication channels can strengthen working relationships, increase partner satisfaction, and build long-term loyalty.